Periosteal Sharpey’s fibers: a novel bone matrix regulatory system? - Aaron, Jean E. (Frontiers in Endocrinology, 2012)
Sharpey’s “perforating” fibres (SF) are well known skeletally in tooth anchorage. Elsewhere they provide anchorage for the periosteum and are less well documented. Immunohistochemistry has transformed their potential significance by identifying their collagen type III (CIII) content and enabling their mapping in domains as permeating arrays of fibres (5-25 microns thick), protected from osteoclastic resorption by their poor mineralization. As periosteal extensions they are crucial in early skeletal development and central to intramembranous bone healing, providing unique microanatomical avenues for musculoskeletal exchange, their composition (eg collagen type VI, elastin, tenacin) combined with a multiaxial pattern of insertion suggesting a role more complex than attachment alone would justify. A proportion permeate the cortex to the endosteum (and beyond), fusing into a CIII-rich osteoid layer (<2 microns thick) encompassing all resting surfaces, and with which they apparently integrate into a PERIOSTEAL-SHARPEY FIBRE-ENDOSTEUM (PSE) structural continuum. This intraosseous system behaves in favour of bone loss or gain depending upon extraneous stimuli (ie like Frost’s hypothetical “mechanostat”). Thus the birefringent fibres are sensitive to humoral factors (eg oestrogen causes retraction, rat femur model), physical activity (eg running causes expansion, rat model), ageing (eg causes fragmentation, pig mandible model) and pathology (eg atrophied in osteoporosis, hypertrophied in osteoarthritis, human proximal femur), and with encroaching mineral particles hardening the usually soft parts. In this way the unobtrusive periosteal SF network may regulate bone status, perhaps even contributing to predictable “hotspots” of trabecular disconnection, particularly at sites of tension prone to fatigue, and with the network deteriorating significantly before bone matrix loss.